PRAGMATIC REFERENCE IN LITERARY DISCOURSE - Qosimova , Nafisa Farxodovna; Haydarova , Gulnora Rajabovna (Innovative Development in Educational Activities, 2023)
This article is devoted to discourse analyses which discusses the reference and its main types. Particularly, this study aims at showing the importance of raising learners‟ awareness as to the use of cataphoric references in discourse. In addition, it studies the reference and its types comparatively and finds out similarities and dissimilarities of the reference in the Uzbek and English languages. And, in accordance with what has shortly explained above, this paper will also try to answer these questions: [1] what is the definition of reference ? [2] What are features of it and some examples of reference in literary discourse?